Program Pelatihan Dan Konsultasi Bisnis Tentang Produksi Bersih Dan Laporan Keuangan Pada Usaha “Istana Rendang” Di Kenagarian Mungka Kabupaten Lima Puluh Kota - Ratni Prima Lita; Yulia Hendri Yeni; Laura Syahrul (Jurnal Pengabdian Warta Andalas, 2016)
The entrepreneur of Istana Rendang Kenagarian Mungka, Kabupaten Limapuluh Kota has various limitations in running a business, particularly the ability of its resources (production and finance management). The activity have the objective as folows: To develop ability entrepreneur of Istana Rendang to have cleaner production. To develop ability entrepreneur of Istana Rendang to arrange financial report. The method of this activity has done in several ways: training and business consultation. The entrepreneur of Istana Rendang Kenagarian Mungka as the object of this activity. They are active and interest to cleaner production and to arrange financial report. Keywords: Cleaner Production, Laporan keuangan